Analisis Strategi Pemasaran PT. Vivo Communication Indonesia Area Garut dengan Metode Swot dan Matriks BCG - Tatang Mulyana (Jurnal Wacana Ekonomi, 2017)
PT. Vivo communication Indonesia has a problem with its existence. In determining the marketing strategy to become the top three smartphone companies in Indonesia, of course, to be the best the company must also be good in marketing lines in every region in Indonesia, one of which is in the Garut area. This study aims to analyze the marketing that can be done by PT. Vivo communication Indonesia Garut Area based on the STP strategy, Marketing Mix, SWOT analysis and BCG matrix. SWOT analysis is done by analyzing external and internal factors while the BCG matrix is carried out based on the sales report of PT. Vivo communication Indonesia Garut Area 2015-2016 which is compared to the sales report of competitors, namely the Oppo Garut Area to determine the level of market growth and market share. The results of the research from the BCG matrix analysis show that the Vivo Area Garut market growth rate is 11.78% and its market share is 0.95 against its competitors, the Oppo Garut Area, so that it is in the question mark quadrant, a strategy that can be carried out by expanding the market and working with more stores. existing in Garut Regency so the opportunity to reach the market is higher. Then increase the number of advertisements in the field to form an understanding to the wider community about Vivo smartphones. From the SWOT analysis, it is known that the SO strategy that can be used is to build brand awareness and increase consumer knowledge of Vivo about its strengths. WO strategies that can be used are establishing service center facilities and working with vendors to help branding and increase further sales. The ST strategy that can be used is to continuously improve quality. Increase the ease of warranty and improve after-sales service WT strategies that can be used are recruiting competent promoters and changing the image of new products with promotions and events.